Comparison of Common Methodologies for the Determination of Knee Flexor Muscle Strength - Dan I Ogborn; Alix Bellemare; Brittany Bruinooge; Holly Brown; Sheila McRae; Jeff Leiter (International Journal of Sports Physical Therapy)
# Background